2007
DOI: 10.1161/hypertensionaha.107.097634
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Precursor A Gene Polymorphisms and Risk of Blood Pressure Progression and Incident Hypertension

Abstract: Abstract-We tested the hypothesis that natriuretic peptide precursor A gene polymorphisms are significantly associated with blood pressure progression and incident hypertension among healthy, middle-aged women. We performed a prospective cohort study among 18 437 white women participating in the Women's Health Study who were free of hypertension at baseline. Two previously characterized single nucleotide polymorphisms within the natriuretic peptide precursor A gene (rs5063 GϾA and rs5065 TϾC) were genotyped. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…The strategy was initially designed to increase the chance of finding genes predisposing to ischemic stroke and cerebral hemorrhage independent of blood pressure. In addition, it has been noted that in a large-scale prospective study, the A allele of NPPA rs5063 has provided a protective effect for blood pressure progression in 48 months and incident hypertension for the entire follow-up[41]. Qian ea al, reported that in a meta-analysis that MTHFR rs1801133 was significantly associated with hypertension among both the European and East Asian adult population [42].…”
Section: Discussionmentioning
confidence: 99%
“…The strategy was initially designed to increase the chance of finding genes predisposing to ischemic stroke and cerebral hemorrhage independent of blood pressure. In addition, it has been noted that in a large-scale prospective study, the A allele of NPPA rs5063 has provided a protective effect for blood pressure progression in 48 months and incident hypertension for the entire follow-up[41]. Qian ea al, reported that in a meta-analysis that MTHFR rs1801133 was significantly associated with hypertension among both the European and East Asian adult population [42].…”
Section: Discussionmentioning
confidence: 99%
“…Of these genetic variants, two known missense variants (rs5063 and rs5065) in the NPPA gene have been shown to be associated with hypertension [15,16], coronary heart disease [30], stroke [31,32], and response to diuretic therapy [17]. In addition, several other SNPs at the NPPA-NPPB locus (rs198388, rs198389, rs6668352) [33] and the NPPC (rs5268) [34], NPRA (rs28730726) [35] and NPRC genes (rs700923) [33] were reported to be associated with the risk of left ventricular dysfunction after primary coronary artery bypass grafting and with the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Extension products were purified by a 15-min incubation with 1 U of shrimp alkaline phosphatase (Promega, Madison, Wisconsin, USA) at 37 °C and a subsequent 15-min incubation at 80 °C to inactivate the enzyme. The purified products (0.5 μL) were mixed with 9 μL of formamide and 0.5 μL of GeneScan-120 LIZ Size Standard (Applied Biosystems) and separated 15,16], and response to diuretic therapy [17]. In addition, the minor alleles of two highly linked polymorphisms (T555I/Q568P) in the Corin gene were reported to be associated with increased risk of hypertension and enhanced cardiac hypertrophic response to pressure overload in African Americans [18,19].…”
Section: Genotypingmentioning
confidence: 99%
“…notably, two common genetic variants that create nonsynonymous amino acid changes within nPPa, rs5063, and rs5065 had previously been implicated in conditions associated with af. 55, 56 a small Chinese study had suggested that the presence of rs5063 resulted in an increased risk of af. 57 however, our study involving 620 af cases and 2,446 controls found no association between either single nucleotide polymorphism (snp) and the risk of af.…”
Section: Mechanistic Subclass Of Af 5: Anp Modulation Of Atrial Electmentioning
confidence: 99%